2011
DOI: 10.1016/j.jtcvs.2010.07.096
|View full text |Cite
|
Sign up to set email alerts
|

Management of esophageal anastomotic leaks, perforations, and fistulae with self-expanding plastic stents

Abstract: In combination with effective interventional or surgical drainage, stenting is a viable option for the treatment of esophageal anastomotic leaks and perforations, but the success in tracheoesophageal fistula is limited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(36 citation statements)
references
References 25 publications
(25 reference statements)
0
36
0
Order By: Relevance
“…Due the risk of mediastinal contamination during endoscopy, it is recommended that esophageal stents be placed at time of initial endoscopic diagnosis. [30] The morbidity associated with endoscopic management and stenting extends to the required follow-up and often the need for repeat interventions. Serial surveillance chest radiography is required to monitor for stent migration, and when detected, repeat endoscopy is required to reposition the stent.…”
Section: Analysis Of Data Regarding the Safety Efficacy And Indicatmentioning
confidence: 99%
See 1 more Smart Citation
“…Due the risk of mediastinal contamination during endoscopy, it is recommended that esophageal stents be placed at time of initial endoscopic diagnosis. [30] The morbidity associated with endoscopic management and stenting extends to the required follow-up and often the need for repeat interventions. Serial surveillance chest radiography is required to monitor for stent migration, and when detected, repeat endoscopy is required to reposition the stent.…”
Section: Analysis Of Data Regarding the Safety Efficacy And Indicatmentioning
confidence: 99%
“…Dai and colleagues demonstrated that in their series, repeat stenting was necessary in 33 of 40 patients, the mean number of stents per patient was 3.2, and the mean time to healing was 30 days. [30] The principle advantage of endoscopic stenting is immediate coverage of the anastomotic defect with shorter time to oral intake. Freeman and colleagues demonstrated that 82% of patients were able to resume oral intake within 72 hours of stent placement.…”
Section: Analysis Of Data Regarding the Safety Efficacy And Indicatmentioning
confidence: 99%
“…In two studies, oral intake was initiated at approximately 3 days after covered stent placement for esophageal perforations. 71,72 We believe oral intake of liquids can be resumed on the fourth or fifth day. Surgical intervention is mandatory if endoscopic closure or stent diversion is not possible or is unsuccessful or in the setting of clinical deterioration despite endoscopic and percutaneous (see the following) intervention.…”
Section: Esophageal Perforations Beyond the Proximal Esophagusmentioning
confidence: 99%
“…However, success with this option is limited. 14 If the fistula does not respond to conservative measures, surgical closure may be necessary. Jacobs et al described a submucosal purse-string suture that had an 80% success rate in their 20 patients.…”
Section: Discussionmentioning
confidence: 99%